PAHAM QADARIYAH DAN JABARIYAH PADA PELAKU PASAR PELELANGAN IKAN BAJO DI KABUPATEN BONE, PROVINSI SULAWESI SELATAN - Muhammad Hasbi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This research applies descriptive method for describing or explaining a problem and phenomenon which exist until now. The issues discussed in this research are: 1). How is society’s view on Qadariya and Jabariya doctrines? 2). How is the role of Qadariya and Jabariya theology towards society at Bajo Fish Auction market? This result concludes that based on Islamic perspective, human deeds are interpreted into viewpoints. Human beings have a freedom and desire to do some deeds that they want. They create their deeds. It is called Qodariya doctrine. Conversely, the second group’s view point is different. They think that human beings cannot make their own deeds but God can make them. For this group, man cannot do anything, they dont have the power to do anything because they are controlled by God. Their thought is called Jabariya. Some societies of Bajo fish auction market agree to one or both of them to view those doctrines. Some of them also have different point of view towards those doctrines.